Enhancing Marketing Performance Through Risk Management In MSMEs - Wibowo, Sarwo Eddy; Aksenta, Almasari (Sean Institute, 2024)
This study aims to examine the implementation of business risk management for enchance marketing performance in Harum Laundry MSMEs. The analysis was conducted on various aspects of risks such as financial, operational, marketing, and product faced by Harum Laundry MSMEs. The method used in this research is a qualitative approach by collecting data through interviews. The results of the analysis identified that the biggest risk is related to finance, where reliance on personal capital can result in disruption to business operations. The research also offers solutions in controlling these risks by proposing cooperation with business partners as an anticipatory measure against possible business failures. It is hoped that the results of this study will not only provide benefits for entrepreneurs to implement risk management in their businesses, but also increase understanding of the importance of risk management in the business context.